2015
DOI: 10.1542/peds.2014-3925
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Decrease Pertussis Transmission to Infants

Abstract: The Global Pertussis Initiative (GPI) is an expert scientific forum addressing the worldwide burden of pertussis, which remains a serious health issue, especially in infants. This age cohort is at risk for developing pertussis by transmission from those in close proximity. Risk is increased in infants aged 0 to 6 weeks, as they are too young to be vaccinated. Older infants are at risk when their vaccination schedules are incomplete. Infants also bear the greatest disease burden owing to their high risk for per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 48 publications
(28 reference statements)
0
92
0
10
Order By: Relevance
“…25 Boğmaca enfeksiyonunun önlenmesinde koza stratejisinin başarıya ulaşmasını engelleyen bir takım faktörler bulunmaktadır. 27 Bunlardan en önemlisi, koza stratejisinin maliyetinin yüksek olmasıdır. 12,27 İspanya'da yapılan bir çalışmada, koza stratejisinin maliyetinin maternal immünizasyo-nun maliyetinden yaklaşık iki kat fazla olduğu bildirilmiştir.…”
Section: Koza Strateji̇si̇ (Cocooning Strategy)unclassified
See 2 more Smart Citations
“…25 Boğmaca enfeksiyonunun önlenmesinde koza stratejisinin başarıya ulaşmasını engelleyen bir takım faktörler bulunmaktadır. 27 Bunlardan en önemlisi, koza stratejisinin maliyetinin yüksek olmasıdır. 12,27 İspanya'da yapılan bir çalışmada, koza stratejisinin maliyetinin maternal immünizasyo-nun maliyetinden yaklaşık iki kat fazla olduğu bildirilmiştir.…”
Section: Koza Strateji̇si̇ (Cocooning Strategy)unclassified
“…27 Bunlardan en önemlisi, koza stratejisinin maliyetinin yüksek olmasıdır. 12,27 İspanya'da yapılan bir çalışmada, koza stratejisinin maliyetinin maternal immünizasyo-nun maliyetinden yaklaşık iki kat fazla olduğu bildirilmiştir. 12 İtalya'da yapılan bir çalışmada, koza stratejisinin çok kaynak gerektiren pahalı bir yaklaşım olduğu belirtilmiştir.…”
Section: Koza Strateji̇si̇ (Cocooning Strategy)unclassified
See 1 more Smart Citation
“…La disminución de la inmunidad inducida por la vacuna ha desplazado el pico de incidencia en los neonatos hacia los adolescentes y adultos; por otro lado, los brotes nosocomiales de la enfermedad no son infrecuentes y los trabajadores en el cuidado de la salud al ser expuestos se convierten en fuente de infección especialmente a infantes con pobre desarrollo inmunológico, como es el caso de los neonatos prematuros (17,18).…”
Section: Epidemiologíaunclassified
“…50 The Global Pertussis Initiative, an international expert group on pertussis, recommended the MV as a first-line intervention, and cocoon strategy as a second line to decrease pertussis in infants in 2015. 51 The WHO demonstrated that the MV is an important costeffectiveness strategy for preventing pertussis in infants who do not yet receive the regular vaccination schedule. 8 This coincides with the findings of Vilajeliu, who found a strong correlation between levels of IgG-BP antibodies in mothers and in their infants.…”
Section: Security and Cost/effectivenessmentioning
confidence: 99%